Heat transfer enhancement and entropy generation analysis of bionic fish-scale structures in narrow rectangular channels for plate-type fuel applications - Xiaoya Liu; Lingke Ran; Xinwen Zhao; Hongguang Xiao; Yongfa Zhang; Ming Ding (Annals of Nuclear Energy, 2026)

Multi-scale analysis of seed dormancy in Lonicera maackii and functional identification of LmABI5 in promoting dormancy - Ruoxin Duan; Ruofan Li; Jing Xu; Ran Zhao; Yanrui Ge; Yifan Liu; Ruili Li (Plant Science, 2026)

Simultaneous elimination of sulfonamides and antibiotic resistance genes via peroxymonosulfate activation by ligand-modulated iron sites on biochar: The critical role of interfacial EDTA complexation - Yifan Liu; Fengxia Yang; Xue Li; Zhikang Deng; Xi Chen; Minghui Xiang; Ran Zhao; Xiaoquan Mu; Yongzhen Ding; Junjie Wang; Zulin Zhang (Chemical Engineering Journal, 2026)

A bubble-propelled microneedle patch with photothermal-controlled NO release for eradicating biofilms in diabetic wounds - Xiaojuan Zhao; Yi Li; Zhichao Ran; Peihang Song; Junpei Mei; Wenwei Liu; Chaoqun Liu; Ningning Song; Yanwei Yang (Chemical Engineering Journal, 2026)

Recent advances in therapeutic agents for uranium poisoning: a comprehensive review - Juan Li; Wenrun Li; Feng Huang; Qiuchi Wang; Hongjia Liu; Liyi Chen; Qiuping Wang; Yong Li; Shiyan Fu; Yazhen Zhao; Yonghong Ran; Yuhui Hao (BioMetals, 2026)

Effects of microbivorous nematodes on microbial necromass accumulation under changing precipitation in tropical forests - Qiongjie He; Ning Zhao; Kangle Hou; Qiang Ran; Rentao Liu; Faming Wang; Feng Sun; Yakov Kuzyakov (Applied Soil Ecology, 2026)

Cross-scale mapping of Leaf Nitrogen Content in arid desert shrubs by integrating UAV and satellite data under sparse sample conditions - Chenglong Xin; Jie Bai; Hongwei Zheng; Ran Liu; Yongbo Zhao; Duoyuan Shi; Jinfeng He; Yong Zhu (International Journal of Remote Sensing, 2026)

Comparative transcriptome analysis identifies ABA/ethylene signaling components and WGCNA hub genes underlying defoliant sensitivity in Gossypium barbadense - Caixia Li; Meng Wang; Zixin Zhou; Zhiqing Liu; Jianping Li; Yaohua Li; Yahui Deng; Yifan Wang; Lingfang Ran; Jiahui Zhu; Alifu Aierxi; Weiran Wang; et al. (Plant Gene, 2026)

Differential effects of Cl- and SO42- anion systems on Ca2+-Mg2+-Mn2+ carbonate biomineralization induced by the halophilic Bacillus dokdonensis: Implications for Mn2+-containing saline wastewater treatment - Xueting Chen; Yueming Zhao; Hui Zhao; Memon Kashif Ali; Ran Shu; Bo Liu; Boyu Cai; Runxi Yin; Zuozhen Han; Huaxiao Yan (Journal of Hazardous Materials, 2026)

PAN4, an AI-designed host-directed immunomodulatory peptide, promotes PGRP-SC1a-associated intestinal immune homeostasis in Drosophila melanogaster - Yanying Sun; Yanan Wei; Wenjie Jia; Xinyue Zhou; Ran Dong; Zekun Wu; Hongyu Miao; ZhenZhi Li; Zheng Chen; Chaoran Liu; Weijie Yuan; Ying Hu; et al. (Insect Biochemistry and Molecular Biology, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Lower-molecular-weight yeast mannan polysaccharides beneficially modulate gut microbiota and fermentation profiles in broilers: An in vitro and in vivo assessment - Junwei Bao; Luqian Gong; Yuhua Zhao; Ran Wang; Jing Bai; Jinlong Liu (Biocatalysis and Agricultural Biotechnology, 2026)

A decision-support framework for balancing growth, profit and environmental impacts in aquaculture feeding - Chunlin Chen; Youbang Guan; Lihua Song; Guoping Lian; Daoliang Li; Ran Zhao; Lian X. Liu; Michael Short (Aquacultural Engineering, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

A vascular-on-a-chip system recapitulates endothelial injury following ischemic reperfusion - Qiao Liu; Guoliang Ying; Chenyan Hu; Hongze Li; Ran Liu; Chan Yang; Lingyu Du; Huaiyi Zhang; Wenlei Zhao; Peng Qiao; Zehong Yang; Di Huang; et al. (Chemical Engineering Journal, 2026)

Effects of salinity management practices on the soil organic carbon stock in China's salinized soils: A meta-analysis - Wenchao Zhang; Ran Li; Yangyang Sun; Zhentao Sun; Shujuan Wang; Jia Liu; Yan Li; Lizhen Xu; Yonggan Zhao (CATENA, 2026)

Climate-driven changes in city-scale building energy demand under urban-adjusted future climate scenarios - Linzhi Zhao; Abudureheman Abuduwayiti; Yanyi Zhu; Ke Liu; Ran Zhang; Chang Xu; Xiaodong Xu (Sustainable Cities and Society, 2026)

W/O/W emulsion-filled egg white gel co-stabilized by protein and γ-cyclodextrin MOFs with multi-chamber encapsulation potential - Chan Li; Xue Yang; Yunfei Zou; Li Zhang; Chuhuan Wei; Yan Ran; E Zhao; Jibiao Yuan; Keshan Wang; Yongguo Jin; Ying Zhou; Qiujin Zhu; et al. (Food Research International, 2026)

Photothermal-responsive Au nanorod-silica nanocomposite with on-demand curcumin release for sequential therapy of biofilm infections - Wenhui Jiang; Shunlan Luo; Kehan Du; Kai Yuan; Yuanhua Cong; Xiaoping Zeng; Dawei Wang; Hongyang Zhao; Huinan Suo; Liu Yang; Xiaowen Ou; Hao Jiang; et al. (Chemical Engineering Journal, 2026)

Temsirolimus safety evaluation: real-world adverse event analysis from the FDA adverse event reporting system database - Lifeng Dan; Zhenyu Liu; Zecang Zhao; Yueli Ran; Jiangtao Zhou; Dongyang Li; Renjie Zhou; Shuai Su; Zhikang Yin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Electrolyte-driven H₂O₂ boost in plasma activated water: The role of sulfate in plasma electrolysis - Tailin Ren; Kun Liu; Congfu Ran; Xiangyu Ma; Jianan Zhao; Renwu Zhou; Patrick J. Cullen (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

A remote sensing framework unveiling the life-cycle dynamics and environmental drivers of Ulva prolifera green tides in the South Yellow Sea - Yijie Tang; Mengquan Wu; Jie Zhao; Shaopeng Luan; Pengsen Yang; Longxing Liu; Bowen Liu; Jinyi Lv; Gang Chen; Hongyu Kan; Yuying Ran; Huining Lai (Marine Environmental Research, 2026)

Sustainable management of plateau mountainous urban agglomerations based on the ecosystem services supply-demand balance: Application of scale and threshold effects - Xiaobao Wang; Xiaoqing Zhao; Yuju Ran; Yanmin Fan; Wentao Li; Xianmin Ye; Yuqin Zhou; Yanlin Wang; Fei Liu (Journal of Cleaner Production, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Pressure-driven flavor formation in rapeseed oil: an integrated multi-omics approach - Yini Yang; Chang Zheng; Ran Zhao; Ya Xu; Lanhang Yao; Wenlin Li; Changsheng Liu; Chuyun Wan; Qi Zhou (Food Chemistry, 2026)

Nondecomposer-mediated nutrient transfer in soils: experimental evidence from Drosophila - Yunchao Luo; Run Liu; Tingting Cao; Jiayue Zhang; Mengna Zhao; Ke Li; Zunian Ran; Lin Wang; Xingjun Tian (Applied Soil Ecology, 2026)

The effect of bile salts stress on the biology and transcriptome characteristics of Vibrio parahaemolyticus under low salt environment - Zhiyong Song; Ran Zhang; Shiying Ji; Zhengchuan Long; Yingjie Pan; Qingchao Xie; Yong Zhao; Haiquan Liu (Archives of Microbiology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Integrated network toxicology, molecular docking, molecular dynamics simulation, and experimental verification to elucidate the mechanism of hepatotoxicity and processing detoxification in Fructus Meliae Toosendan - Shan Ran; Dongshi Gu; Yuhan Zhao; Yujuan Liu; Ning Zhang (Toxicon, 2026)

A scalable and efficient framework for city-scale building energy modeling with microclimate considerations - Ke Liu; Xiaodong Xu; Deqing Lin; Ran Zhang; Linzhi Zhao; Abudureheman Abuduwayiti; Francesco Causone (Sustainable Cities and Society, 2026)

AnchorReF: A novel anchor-based visual re-localization framework aided by multi-sensor data fusion - Hao Wu; Yu Ran; Xiaoxiang Zhang; Xinying Luo; Li Wang; Teng Zhao; Yongcheng Song; Zhijun Zhang; Huisong Zhang; Jin Liu; Jian Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Hydrogen sulfide-based nanotheranostics: A multifunctional platform for cancer diagnosis and therapy - Wen Ran; Yan Zhao; Ruiping Huang; Enhao Cao; Junjie Zhou; Jiang Yu; Hongzhuo Liu; Yongjun Wang (Chemical Engineering Journal, 2026)

Hydroxyl-enriched cerium oxide-chitosan hybrid macroporous beads for arsenite deep removal: Batch and column adsorption - Ting Wang; Maosong Zhao; Ran An; Kong Yang; Yuanfeng Wei; Jie Luo; Chengbin Liu; Xiaolong Liu; Kai Yin (Chemical Engineering Journal, 2026)

Low-temperature mineral engineering stabilizes anchored cobalt sites for ultrafast antibiotic destruction via electron transfer-driven radical/nonradical synergy - Liyao Ren; Ran Liu; Runbin Zeng; Lingling Cao; Wenyu Wang; Xuguang Li; Xing Xu; Yanxia Zhao; Liangguo Yan; Yanfei Li; Wen Song (ENGINEERING Environment, 2026)

Boosting coalbed methane recovery through nanofluid-mediated pore and interfacial regulation - Jiajia Zhao; Shixiang Tian; Yihong Wen; Ting Liu; Tong Liu; Xuan Zhang; Tengfei Ma; Qican Ran (Process Safety and Environmental Protection, 2026)

Recent advances and prospects of iron-based biochar for antibiotic removal: Unveiling the dual mechanisms of adsorption and degradation - Junjie Wang; Yifan Liu; Xue Li; Ran Zhao; Xiaoquan Mu; Fengxia Yang; Haixin Guo; Yongzhen Ding (Journal of Environmental Chemical Engineering, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Thermo and LDL-responsive acrylated β-cyclodextrin based microspheres enable targeted oleanolic acid release and LDL removal for atherosclerosis therapy - Yujie Xiao; Xianda Liu; Ziyue Ling; Shifan Chen; Ran Wei; Weifeng Zhao; Changsheng Zhao (Chemical Engineering Journal, 2026)

Synthesis, evaluation and preliminary clinical study of novel 68Ga-labeled Nectin-4 targeting PET tracer - Geng Hu; Zexin Xu; Da-Yong Hou; Pengcheng Ran; Liang Cheng; Wei Liu; Yue Zhao; Fan Jia; Xinyue Yang; Huihui You; Baoyuan Li; Hongxin Li; et al. (Chemical Engineering Journal, 2026)

Genome-wide association study of alkali tolerance at germination stage in wheat - Haoran Gu; Zixu Wang; Xiaotong Liu; Haotian Cao; Zixin Zhou; Meishan Zhou; Xinzhi Yang; Han Sun; Ran Qin; Chunhua Zhao; Yongzhen Wu; Fa Cui (Theoretical and Applied Genetics, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Synergistic dual-network design of a nanocomposite hydrogel electrolyte for durable and flexible zinc–air batteries - Wei Lu; Qingye Liu; Cheng Ran Li; Jiangtao Li; Wei Zhao; Yilun Liu (Chemical Engineering Journal, 2026)

Genome-wide association study and transcriptomic analysis reveal new genes for unsaturated fatty acid contents in soybean - Runqing Duan; Junqi Liu; Yanan Dai; Ran Duan; Liang Dong; Yinghua Sheng; Qingwei Zhang; Huibing Huang; Yinyue Zhao; Liang Zhang; Xianzhi Wang (Theoretical and Applied Genetics, 2026)

Dynamic brain functional connectivity in age-related hearing loss during auditory selective spatial attention - Hongxing Liu; Yanru Bai; Mingkun Guo; Ran Zhao; Jianing Zhu; Guangjian Ni (GeroScience, 2025)

Can urban-rural public services drive the realization of sustainable development goals? An empirical study of a typical rural‒urban integration pilot area in China - Huiping Ran; Rui Liu; Li Xing; Yifei Zhao; Kunlian Zhang (Journal of Rural Studies, 2025)

Acid and antibiotic stress suppresses soil microbial carbon use efficiency via fungal proliferation: Mechanistic insights from microbial community dynamics - Fengwu Zhou; Xiangmei Zhai; Zongren Dai; Ming Zhou; Ziyi Zhao; Ran Liu; Xinrui Zhang; Shuai Zhang; Zezhen Pan; Wenhui Zhong; Zheng-Shuang Hua; Ming Nie; et al. (Journal of Hazardous Materials, 2025)

A network approach to promoting cold island connectivity for mitigating the urban heat island effect: Key areas and targeted strategies - Yankai Huang; Jingkai Huang; Yaling Huang; Tongyan Li; Chengyu Ran; Jiali Jin; Shuang Zhao; Yuxiang Liu; Weicong Fu (Journal of Environmental Management, 2025)

Nano-silicon mitigates sulfamethoxazole-induced stress in wheat seedlings: Integrated transcriptomic and metabolomic analysis - Qianqian Liu; Ziting Jin; Xinyu Liao; Jie Feng; Zhiheng Li; Wenlu Zhao; Yaxin Zhu; Ran Wu; Shaoting Du; Huijun Liu (Journal of Environmental Chemical Engineering, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

Evaluation of Lentilactobacillus kefiri NM119–2 as a novel probiotic in fermented milk: functional properties and metabolic impact - Baoyi Yuan; Xiangyun Liu; Jianan Li; Ran Gao; Xin Zhao; Lai-Yu Kwok; Qiuhua Bao (Food Research International, 2025)

Cocatalyst-free hydrogen evolution over benzothiazole-based metal covalent organic framework under visible light - Chunting Zhao; Ran Shi; Xingyan Yang; Jianhong Zhao; Shan Zeng; Zhishi Qiu; Yumin Zhang; Qingju Liu (Chemical Engineering Journal, 2025)

A self-activated CO-releasing microneedle patch for treating diabetic foot ulcer biofilm infection - Linpei Li; Menghao Wei; Haixia Zhang; Zilong Zhang; Xiaojuan Zhao; Zhichao Ran; Yi Li; Yanwei Yang; Ningning Song; Chaoqun Liu (Chemical Engineering Journal, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Machine learning decoding of electronic thresholds in prediction of oriented generation of solar-induced oxidative reactive species and antibiotics degradation - Hao Bi; Zhiruo Zhou; Qian Liu; Ran Zhao; Fangyuan Chen; Jun Zhang; Zhurui Shen (Journal of Hazardous Materials, 2025)

Satellite remote sensing capturing intense ozone production over marginal seas in East Asia: evident influence on air quality in coastal cities - Jin Ye; Qihou Hu; Qin Gao; Ran Zhao; Wenjing Su; Chengxin Zhang; Xiaohan Wang; Ziwei Li; Cheng Liu (Atmospheric Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

A Novel Felbinac Transdermal Patch with High Permeability: Design, Development and Evaluation - Li Qin; Cheng Liu; Ran Bai; Zhining Zhao; Yinghua Sun; Peng Zhang (AAPS PharmSciTech, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Late glacial to Holocene vegetation history and quantitative reconstruction of climate in semiarid areas of China: A case study of Angulinur Lake - Xu-Ran Zhang; Hua-Yong Zhang; Zhao Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

Progression of the Residual Lesion in Cavernous Sinus Extra-Axial Cavernous Hemangioma After Surgery - Ran Huo; Qifeng Yu; Hongyuan Xu; Jie Wang; Shaozhi Zhao; Jiancong Weng; Xiudan Bai; Yuming Jiao; Wenqian Zhang; Qiheng He; Zhiyou Wu; Shaowen Liu; et al. (Translational Stroke Research, 2025)

Terrestrial–aquatic microbial community coalescence slows litter decomposition in forest streams - Han Jiang; Yinghui Yang; Jiawen Liang; Run Liu; Yueting Pan; Tingting Cao; Siyuan Chen; Zunian Ran; Chang Zhao; Yanli Tian; Xingjun Tian (Plant and Soil, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Maillard reaction products of Cantharellus cibarius protein hydrolysate as a flavor enhancer: Optimization of the reaction and effects on its flavor - Shujing Liu; Kashif Ameer; Ran Yang; Lingbo Qu; ChangCheng Zhao (International Journal of Gastronomy and Food Science, 2025)

Synthesis of Cu2O/CuZnAl-LDHs heterojunction photocatalyst with enhanced antibacterial efficiency for personal protective equipment - Tian Sun; Xiangkun Ran; Mingyue Cao; Jiaqi Liu; Yanrui Su; Linjun Duan; Dan Liang; Zihao Xia; Wa Gao; Hanqing Zhao (Environmental Research, 2025)

Defect engineering toward binary spinel ZnCo2O4 for boosting electrocatalytic nitrate reduction to ammonia - Qingsong Lai; Zhaomeng Liu; Ahmad Akasa; Xiran Zhao; Ran Wei; Xuan-Wen Gao; Teuku Muhammad Al Wafi; Qinfen Gu; Wen-Bin Luo (Chemical Engineering Journal, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Causal Relationship Between Serum Zinc Levels and Diabetic Kidney Disease (DKD): A Plasma Proteomics Mediation Study - Chunbo Zhao; Tingting Pan; Wei Liu; Fanqian Cheng; Xiaoxuan Zhao; Shuxin Yu; Yi Yang; Ran Zhang; Weixia Sun (Biological Trace Element Research, 2025)

Selective electroreduction of carbon dioxide to ethylene over stable iodide-induced asymmetric copper sites within a metal-organic polyhedron - Yaguang Peng; Yinlin Chen; Zi Wang; Yaoyu Yin; Jiangnan Li; Huanyan Liu; Jiapeng Jiao; Wenling Zhao; Ran Duan; Pei Zhang; Jiahao Yang; Hengan Wang; et al. (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Angular effect correction of remotely sensed land surface temperature by integrating geostationary and polar-orbiting satellite data - Ran Wei; Si-Bo Duan; Xiangyang Liu; Niantang Liu; Xiaoxiao Min; Zhao-Liang Li (Remote Sensing of Environment, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Strip application of organic fertilizer in the root zone increases the substitution ratio of chemical nitrogen and sunflower yield in saline-alkali soil - Ran LI; Shujuan WANG; Jia LIU; Erzhen LI; Junxia MIAO; Xiaoliang WEN; Jing YANG; Lizhen XU; Binrui LI; Cunwang JIN; Yan LI; Yonggan ZHAO (Pedosphere, 2025)

Vascular-tissue-specific expression of an endo-1,4-β-xylanase enhances forage efficacy of sweet sorghum silage - Fengyong Ge; Huimin Wei; Wenzhe Zhang; Cuo Mei; Yihong Gao; Hanlei Yang; Xuekai Wang; Jingwen Cao; Zhuolin Liu; Jiayang Shi; Ran Xia; Kangxu Zhao; et al. (Molecular Plant, 2025)

Melamine derivatives in indoor dust from China: Temporal trends and human exposure before and during COVID-19 pandemic - Ke Xu; Keyi Li; Yixuan Shi; Ran Ding; Yarui Liu; Yumeng Shi; Hongzhi Zhao; Zhipeng Cheng; Hongkai Zhu (Journal of Hazardous Materials, 2025)

Integrating allocation methods and regional optimization in life cycle assessment of floating photovoltaics for cleaner energy transitions in China - Ran Hao; Xin Sun; Yuchen Zhao; Jiahang Shang; Xue Zhu; Hongwei Li; Fengling Liu (Journal of Cleaner Production, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Correction: Mitigation of depleted uranium-induced mitochondrial damage by ethylmalonic encephalopathy 1 protein via modulation of hydrogen sulfide and glutathione pathways - Juan Li; Yong Li; Yazhen Zhao; Suiyi Liu; Wenrun Li; Huanhuan Tan; Li Shen; Yonghong Ran; Yuhui Hao (Archives of Toxicology, 2025)

Tracking phycocyanin dynamics in East Lake using Landsat-8 and generalized additive models: impact of COVID-19 and conservation efforts - Jincan Tang; Wen-Wen Liu; Ran Li; Enmin Zhao; Yi-Ming Kuo (Environmental Monitoring and Assessment, 2025)

Effects of drying on biofilm-mediated sediment stability in intertidal mudflats: transition from biostabilization to biodestabilization - Ran Ge; Yonggang Zhao; Zheng Gong; Suna Wang; Aihong Wei; Mo Peng; Honglei Liu (Sedimentary Geology, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Effect of flocculant addition and organic matter content on flocculation-electroosmotic coupled dewatering of river sludge - Qing Wei; Fuyuan Ran; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2025)

Water solubility in nominally anhydrous minerals in a silica-rich system at the top lower mantle - Luyao Chen; Zhaodong Liu; Xinyu Zhao; Chaowen Xu; Dongyang Ju; Bingtao Feng; Jinze He; Ran Liu; Xinyang Li; Wei Du; Bingbing Liu; Wenliang Xu (Earth and Planetary Science Letters, 2025)

Pueraria thomsonii Benth-Associated Endophytes: A Multifaceted Exploration of Its Bioactive Molecules - Yu Li; Yu Liu; Yalan Ran; Shiqin Peng; Xiaoman Yuan; Lingyun Zhao; Huiru Sun; Fulian Su; Donghai Huang; Saravana Kumar Pachaiyappan; Meijun He (Indian Journal of Microbiology, 2025)

Electrochlorination Fenton-like and Fenton processes for different categories of phosphonates oxidation to orthophosphate: Performance and mechanism characteristics - Sainan Sun; Guanghua Huang; Jiawei Tang; Fazhi Xie; Xiao Wang; Qiang Guo; Hongshuai Kan; Meng Qiao; Yanpeng Liu; Yi Liu; Zixiao Zhu; Xu Zhao; et al. (Journal of Hazardous Materials, 2025)

Tailoring hetero-precursor transformation for simultaneous surface-coating and subsurface-doping of Ni-rich layered oxide cathodes - Junfan Zhang; Ran Wang; Kunkun Guo; Mohan Yang; Zenan Zhao; Jing Wang; Qi Liu; Lai Chen; Ning Li; Yuefeng Su; Feng Wu; Guoqiang Tan (Chemical Engineering Journal, 2025)

Identification, Clinical Values, and Prospective Pathway Signaling of Lipid Metabolism Genes in Epilepsy and AED Treatment - Hong Wei; Biao Jin; Kangren Zhao; Dandan Liu; Jing Ran; Fuling Yan (Molecular Neurobiology, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

Socioeconomic developments drove regime shifts of agriculture–ecology–economy nexus of social-ecological system: Four-decade lessons from southeast China - Xinhua Li; Chong Jiang; Yixin Wang; Xiaohuang Liu; Jie Liu; Jun Wang; Ying Zhao; Yuexin Xiao; Zhiyuan Yang; Ran Wang (Journal of Environmental Management, 2025)

Manganese on P, N self-doped biochar toward promoting periodate activation for highly efficient tetracycline degradation: Performance and mechanisms - Xiaofang Pan; Hong Ma; Rongning Zhang; Ran Deng; Meng Li; Binfei Yang; Ruiying Zhu; Li Zhao; Yong Liu; Xiaobo Gong (Journal of Environmental Chemical Engineering, 2025)

Performance evaluation and discharge pressure discussion of supermarket CO2 refrigeration system integrated with ejector subcooling using solar energy - Deyong Ran; Qichao Yang; Tailan Yin; Liansheng Li; Yuanyang Zhao; Guangbin Liu (International Journal of Refrigeration, 2025)

Electrospun groove shaped fibers with excellent hemocompatibility and highly selective capture of live bacteria from blood - Jianxu Bao; Shifan Chen; Xianda Liu; Ziyue Ling; Chunji Jiang; Zhaoxi Han; Wenjie Wang; Ran Wei; Changsheng Zhao; Weifeng Zhao (Chemical Engineering Journal, 2025)

Predicting Persistent Aneurysm Filling After Pipeline Embolization Device Treatment in Patients with Intracranial Aneurysm: Development and External Validation of a Nomogram Model - Linggen Dong; Chao Wang; Xiheng Chen; Mingtao Li; Tong Li; He Liu; Yang Zhao; Ran Duan; Weitao Jin; Yukun Zhang; Yang Wang; Ming Lv (Translational Stroke Research, 2025)

First satellite observation of total column water vapor from the Chinese Environmental Trace Gases Monitoring Instrument - Ran Zhao; Chengxin Zhang; Wenjing Su; Jin Ye; Ziwei Li; Cheng Liu (Science China Earth Sciences, 2025)

Exploring the anti-inflammatory potential of Lacticaseibacillus paracasei postbiotics: Mechanistic insights and functional components - Yuhang Sun; Zhe Sun; Bing Fang; Ran Wang; Yue Liu; Jingyu Li; Hanglian Lan; Wen Zhao; Wei-Lian Hung; Ming Zhang (Food Bioscience, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Study on the Spatial and Temporal Evolution Law of Large-Size Fracture Propagation in Deep Coalbed Based on Acoustic Emission Technology - Zhihong Zhao; Tianyu Wu; Jianchun Guo; Jiale He; Xiaoyong Wen; Yi Liu; Ran Zhang (Rock Mechanics and Rock Engineering, 2025)

Mitigation of depleted uranium-induced mitochondrial damage by ethylmalonic encephalopathy 1 protein via modulation of hydrogen sulfide and glutathione pathways - Juan Li; Yong Li; Yazhen Zhao; Suiyi Liu; Wenrun Li; Huanhuan Tan; Li Shen; Yonghong Ran; Yuhui Hao (Archives of Toxicology, 2025)

Assessing the Impacts of the Israeli–Palestinian Conflict on Global Sea Transportation: From the View of Mass Tanker Trajectories - Bing Zhang; Xiaohui Chen; Haiyan Liu; Lin Ye; Ran Zhang; Yunpeng Zhao (Journal of Marine Science and Engineering, 2025)
Sea transportation plays a vital role in global trade, and studying the impact of emergencies on global sea transportation is essential to ensure the stability of trade. At present, the conflict between Palestine and Israel has attracted extensive attention worldwide. However, there is a lack of specific research on the impact of conflict on shipping, particularly on global shipping costs. By using the global vessel trajectory data of tankers from the Automatic Identification System (AIS) and taking the global sea transportation of large tankers as an example, this paper quantifies and visualizes the changes in global sea transportation before and after conflicts from a data-driven perspective. Firstly, the complete vessel trajectory, as well as the port of departure and the port of destination are extracted. Then, from the perspective of shipping cost and vessel traffic flow, we evaluate the vessel traffic flow changes caused by the conflict by using the route distance to replace the shipping costs and quantify the cost increase for the relevant countries caused by the vessel detour based on the shipping cost increment index. The research results show that after the outbreak of the conflict, the number of vessels passing through the Red Sea area has decreased significantly. About 3.1% of global vessels were affected, with global sea transportation costs of large tankers increasing by about 0.0825%. This study takes the Israeli–Palestinian conflict as an example and analyzes the impact of emergencies on the global sea transportation situation of tankers based on AIS data. The research results reveal the characteristics of international shipping to a certain extent and provide guidance for global sea transportation route planning.

AIS data-driven analysis for identifying cargo handling events in international trade tankers - Ran Zhang; Daozhu Dong; Xiaohui Chen; Bing Zhang; Yixuan Zhang; Lin Ye; Bing Liu; Ying Zhao; Chunyan Peng (Ocean Engineering, 2025)

Microplastics in fish species from the eastern Guangdong: Implications to Indo-Pacific humpback dolphin (Sousa chinensis) and human health - Jinyan Liu; Qilin Gutang; Yingping Fan; Ran Bi; Puhui Zhao; Keqin Zhang; Zewei Sun; Ping Li; Wenhua Liu; Jianxin Wang (Marine Environmental Research, 2025)

Controls of paleogeomorphology on organic matter accumulation as recorded in Ordovician–Silurian marine black shales in the western South China Block - Feng Liang; Qun Zhao; Qin Zhang; Yuman Wang; Shangwen Zhou; Zhen Qiu; Wen Liu; Bo Ran; Tong Sun (Marine and Petroleum Geology, 2025)

Impact of flocculant compounding on dewatering of river sludge with high water content via flocculation, filter-pressing, and electro-osmotic coupled process - Fuyuan Ran; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Probiotic DNA regulates intestinal Th2 polarization by inducing epithelial cells to produce PD-L1 - Shuo Song; Hanqing Zhang; Le Liu; Minyao Li; Xiangyu Wang; Haotao Zeng; Miao Zhao; Pixin Ran; Qing Shu; Pingchang Yang (Apoptosis, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Insight into the molecular structure construction and pyrolysis mechanism simulation of typical carbonaceous feedstocks for the rapid design and preparation of porous carbon-based materials - Li Zhao; Bo Yuan; Lele Gong; Hongwei Wang; Qiansong Ran; Lingyan Qin; Jiaqi Liu; Luchao Zhang; Kai Li; Guojie Liang; Li Li; Qiang Xie (Fuel, 2025)

Ultra-elastic conductive silicone rubber composite foams for durable piezoresistive sensors via direct ink writing three-dimensional printing - Zehua Zhao; Jiawen Ji; Ying Zhang; Jiwei Liu; Ran Yu; Xin Yang; Xiaojuan Zhao; Wei Huang; Wei Zhao (Chemical Engineering Journal, 2025)

An active-conductive layer stacked sensor platform for real-time detection of heavy metal ions - Yuping Yang; Lijia Xu; Yongpeng Zhao; Yuchao Wang; Zhijun Wu; Zhiliang Kang; Zhiyong Zou; Hui Huang; Yong He; Fei Liu; Zuoliang Tang; Ao Feng; et al. (Chemical Engineering Journal, 2025)

Vessel Type Recognition Using a Multi-Graph Fusion Method Integrating Vessel Trajectory Sequence and Dependency Relations - Lin Ye; Xiaohui Chen; Haiyan Liu; Ran Zhang; Bing Zhang; Yunpeng Zhao; Dewei Zhou (Journal of Marine Science and Engineering, 2024)
In the field of research into vessel type recognition utilizing trajectory data, researchers have primarily concentrated on developing models based on trajectory sequences to extract the relevant information. However, this approach often overlooks the crucial significance of the spatial dependency relationships among trajectory points, posing challenges for comprehensively capturing the intricate features of vessel travel patterns. To address this limitation, our study introduces a novel multi-graph fusion representation method that integrates both trajectory sequences and dependency relationships to optimize the task of vessel type recognition. The proposed method initially extracts the spatiotemporal features and behavioral semantic features from vessel trajectories. By utilizing these behavioral semantic features, the key nodes within the trajectory that exhibit dependencies are identified. Subsequently, graph structures are constructed to represent the intricate dependencies between these nodes and the sequences of trajectory points. These graph structures are then processed through graph convolutional networks (GCNs), which integrate various sources of information within the graphs to obtain behavioral representations of vessel trajectories. Finally, these representations are applied to the task of vessel type recognition for experimental validation. The experimental results indicate that this method significantly enhances vessel type recognition performance when compared to other baseline methods. Additionally, ablation experiments have been conducted to validate the effectiveness of each component of the method. This innovative approach not only delves deeply into the behavioral representations of vessel trajectories but also contributes to advancements in intelligent water traffic control.

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

New insights into uranium biomineralization mediated by Pseudomonas sp. WG2-6 in the presence of organic phosphorus: Promoting effect of extracellular polymeric substance and formation of U-P nanominerals - Lin Zhou; Siyu Hou; XingQi Duan; Yalin Lu; Jiali Liao; Ning Liu; Ran Zhao; Changsong Zhao (Journal of Hazardous Materials, 2024)

Harnessing natural light: Novel nanoheterojunction photocatalyst NaGdF4:Yb,Tm@TiO2/Cu2(OH)2CO3 for actual wastewater remediation - Mengyu Di; Wenqi Liu; Dan Shan; Yue Zhao; Changyuan Zhang; Yankun Wang; Ran Yi; Yang Wu; Jing Zheng; Baiqi Wang (Journal of Environmental Management, 2024)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Gelatin/polyvinyl alcohol films loaded with doubly stabilized clove essential oil chitosomes: Preparation, characterization, and application in packing marinated steaks - Cenchen Ran; Qingqing Li; Mou Zhao; Haotian Cui; Yi Yang; Kui Diao; Yazhi Liu; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Integrated scRNAseq analyses of mouse cochlear supporting cells reveal the involvement of Ezh2 in hair cell regeneration - Yifan Zhao; Ze Xu; Ran Zhang; Mingli Liu; Chengcheng Lu; Chunxin Fan; Jian Wang (Molecular Biology Reports, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

NLRP12 inhibits PRRSV-2 replication by promoting GP2a degradation via MARCH8 - Huiyuan Jing; Yuzhen Song; Erzhen Duan; Jie Liu; Wenting Ke; Ran Tao; Yujin Lv; Pandeng Zhao; Wang Dong; Xianghui Li; Yongbin Guo; Huawei Li (Veterinary Microbiology, 2024)

The interplay between dietary flavonoids and gut microbiota in protecting against heart failure - Jieqiong Zhao; Zhongchao Gai; Juan Zhang; Ran Zhao; Xiaoli Liu; Yan Li (Trends in Food Science & Technology, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Imitation expansion bolts structural bonding interface: Enhancing the bonding properties of bamboo composites through host–guest molecular recognition - Rui Zhao; Tongda Liu; Xin Ran; Jun Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2024)

Microplastics and arsenic speciation in edible bivalves from the coast of China: Distribution, bioavailability, and human health risk - Zhendong Lyu; Xiaohan Chen; Ting Wei; Difeng Wang; Puhui Zhao; Edmond Sanganyado; Duowen Chi; Zewei Sun; Tieyu Wang; Ping Li; Wenhua Liu; Ran Bi (Marine Pollution Bulletin, 2024)

Organic matter composition and stability in estuarine wetlands depending on soil salinity - Lele Wu; Zhaoliang Song; Yuntao Wu; Shaopan Xia; Yakov Kuzyakov; Iain P. Hartley; Yunying Fang; Changxun Yu; Yidong Wang; Ji Chen; Laodong Guo; Zimin Li; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protocatechuic acid enhanced Fe(III) activated peroxymonosulfate system for Sulfamethoxazole degradation in groundwater - Siqi Wang; Ran Wang; Qiutong Lin; Ruixin Liu; Xiaoyu Wu; Guangshan Zhang; Qi Hu; Zhao Jiang; Jianhua Qu; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Zinc oxide nanoparticles and nano-hydroxyapatite enhanced Cd immobilization, activated antioxidant activity, improved wheat growth, and minimized dietary health risks in soil-wheat system - Guangxin Li; Ran Duan; Xinran Liang; Hongen Liu; Shiyu Qin; Long Wang; Haichao Fu; Peng Zhao; Chang Li (Journal of Environmental Chemical Engineering, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Ultrasonic-induced crystallization for efficient extraction of hazardous sodium oxalate with ultra-low alkali loss in alumina industry: From laboratory-scale to continuous pilot-scale - Jianfeng Ran; Yueyu Liu; Jiaping Zhao; Shiwei Li; Haisheng Duan; Ying Chen; Zhiqiang Shi; Shaohua Yin; Libo Zhang (Chemical Engineering Journal, 2024)

Overcoming polarization and dissolution of manganese-based electrodes to enhance stability in electrochemical lithium extraction - Yingjun Qiao; Yonggan Ran; Zhiqiang Qian; Bing Zhao; Chengpeng Li; Zhong Liu (Chemical Engineering Journal, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Fibroblast growth factor receptor 4 deficiency in macrophages aggravates experimental colitis by promoting M1-polarization - Luyao Shen; Cong Wang; Ran Ren; Xudong Liu; Dongqin Zhou; Yu Chen; Yu Zhou; Juan Lei; Yang Xiao; Nan Zhang; Huakan Zhao; Yongsheng Li (Inflammation Research, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Moving forward from escaping the poverty trap in China's greenest regions: Examining four decades of socioecological evolution to re-orient sustainable development policies - Xinhua Li; Chong Jiang; Yixin Wang; Jie Liu; Ran Wang; Ying Zhao; Jie Zhang; Haiyan Zhang; Buqing Wang; Yuexin Xiao (Applied Geography, 2024)

Behavior of calcium lignosulfonate under oxygen pressure acid leaching condition - Sijie Yang; Yuhu Li; Yudong Yang; Ran Liu; Yi Zhao (Hydrometallurgy, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Synergistic use of photocatalysis and convergent paired electrolysis for nickel-catalyzed arylation of cyclic alcohols - Zhao-Ran Liu; Xiao-Yu Zhu; Jian-Feng Guo; Cong Ma; Zhiwei Zuo; Tian-Sheng Mei (Science Bulletin, 2024)

Effects of warming on rice production and metabolism process associated with greenhouse gas emissions - Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Ke Liu; Wentao Shi; Wei Wu; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Extraction and analysis of the sea ice parameter dataset of the Bohai Sea from 2011 to 2021 based on GOCI - Ran Yan; Xi Zhang; Wenlong Bi; Ning Wang; Yiding Zhao; Luchuan Bi; Haipeng Guan; Yunbo Liu; Fuxi Duan; Meijie Liu (Frontiers in Marine Science, 2024)
The Bohai Sea and its surrounding areas are rich in oil and natural gas and play an important role in industry, agriculture and the economy. However, the Bohai Sea suffers severely from sea ice in the winter. While previous research has predominantly focused on methods for retrieving sea ice parameters in the Bohai Sea, analyses of their long-term statistical patterns have been limited. The Geostationary Ocean Color Imager (GOCI) is the first geostationary satellite for ocean color remote sensing, offering high spatial and temporal resolution, which greatly facilitates the extraction of Bohai Sea ice parameters. Utilizing GOCI data, we systematically extracted relevant sea ice parameters for the Bohai Sea region from 2011 to 2021. These parameters include sea ice concentration, sea ice thickness, and sea ice drift. We conducted a comprehensive statistical analysis of the long-term sea ice changes in the Bohai Sea and found that the development process of winter sea ice area is different from the sea ice thickness, and the direction of sea ice drift is basically unchanged. Then we developed statistical models linking sea ice parameters with ocean dynamic factors such as temperature, wind, and drift currents. Among them, the correlation coefficient between the predicted value and the measured value of the sea ice area model is the highest, reaching 0.8382. Furthermore, we examined the previously unexplored relationship between daily sea ice area, sea ice thickness, and accumulated temperature with their respective starting temperatures and accumulation periods. This study provides critical data to support Bohai Sea ice monitoring and marine environmental research. The results of this study contribute to a better understanding of sea ice change trends in the Bohai Sea and inform the development of disaster prevention and mitigation measures.

Promotion strategy of low-carbon multimodal transportation considering government regulation and cargo owners’ willingness - Xinghua Hu; Ruizi Cheng; Jiahao Zhao; Ran Wang; Tingting Zhang; Hao Lei; Ba Liu (Environment, Development and Sustainability, 2024)

LRRK2 is involved in heat exposure-induced acute lung injury and alveolar type II epithelial cell dysfunction - Yindan Wang; Wenjun Fan; Guoqing Zhang; Lisha Zhao; Ting Li; Lu Zhang; Tong Hou; Huihua Hong; Zhenqiang You; Qinghua Sun; Ran Li; Cuiqing Liu (Environmental Pollution, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Systematic foodborne disease prevention and risk management based on infection mechanisms - Ran Liu; Lindu Zhao (Environment, Development and Sustainability, 2024)

Hierarchically porous magnetic biochar as an amendment for wheat (Triticum aestivum L.) cultivation in alkaline Cd-contaminated soils: Impacts on plant growth, soil properties and microbiota - Haichao Fu; Shuanglong Ma; Long Wang; Weijie Xue; Shiwu Xiong; Fuqing Sui; Hongen Liu; Chang Li; Guangxin Li; Ran Duan; Peng Zhao (Chemosphere, 2024)

Self-catalytic decomplexation of Cu−TEPA and simultaneous recovery of Cu by an electrochemical ozone production system using heterojunction Ni-Sb-SnO2 anode - Hongshuai Kan; Ran Mao; Xu Zhu; Yuexin Cui; Yi Liu; Kaifeng Wang; Sainan Sun; Xu Zhao (Journal of Hazardous Materials, 2024)

The impact of regional policy implementation on the decoupling of carbon emissions and economic development - Xiaoyue Ma; Congyu Zhao; Chenchen Song; Danni Meng; Mei Xu; Ran Liu; Yamin Yan; Zhengguang Liu (Journal of Environmental Management, 2024)

Analysis of extracellular and intracellular antibiotic resistance genes in commercial organic fertilizers reveals a non-negligible risk posed by extracellular genes - Ran Zhao; Bingjun Han; Fengxia Yang; Zulin Zhang; Yutao Sun; Xue Li; Yiming Liu; Yongzhen Ding (Journal of Environmental Management, 2024)

Condensation characteristics of ammonia vapor during supersonic separation: A novel approach to ammonia-hydrogen separation - Jiang Bian; Ziyuan Zhao; Yang Liu; Ran Cheng; Xuerui Zang; Xuewen Cao (Fuel, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Roles and sources of B vitamins in the marine ecosystem - Lin Wang; Hancheng Zhao; Ran Bi; Xiaohan Chen; Zhendong Lyu; Wenhua Liu (Reviews in Fish Biology and Fisheries, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Effects of nitrogen application on physicochemical properties of rice starch under elevated temperature - Wenzhe Liu; Kailu Wang; Yufei Zhao; Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Hao Guo; Yanfeng Ding; She Tang (Food Chemistry, 2024)

Environmental surveillance in Jinan city of East China (2014–2022) reveals improved air quality but remained health risks attributable to PM2.5-bound metal contaminants - Zhigang Yu; Zhan Sun; Lanzheng Liu; Chao Li; Xin Zhang; Gzalnur Amat; Mohan Ran; Xiaoyue Hu; Yunxiang Xu; Xiulan Zhao; Jun Zhou (Environmental Pollution, 2024)

The accumulation and carbon sequestration potential of biogenic silica in coastal salt marshes: Implications for relative sea-level rise - Xiangwei Zhao; Xiaodong Zhang; Zhaoliang Song; Lukas Van Zwieten; Xiangbin Ran; Yulin Pu; Jun Sun; Qiang Li; Lele Wu; Xiaomin Yang; Yuqiu Wei; Zimin Li; et al. (CATENA, 2024)

Retention Efficiencies of Vegetative Filter Strips in Reducing Agricultural Nonpoint Source Pollution in Jianghan Plain: Experiments and VFSMOD Modeling - Ran Li; Wen-wen Liu; Enmin Zhao; Yi-Ming Kuo (Water, Air, & Soil Pollution, 2024)

Modification engineering of TiO2-based nanoheterojunction photocatalysts - Yue Zhao; Yue Shu; Xiaoyu Linghu; Wenqi Liu; Mengyu Di; Changyuan Zhang; Dan Shan; Ran Yi; Baiqi Wang (Chemosphere, 2024)

Chromium immobilization and release by pipe scales in drinking water distribution systems: The impact of anions - Ruoling Ni; Xianxian Chu; Ran Liu; Jinlin Shan; Yimei Tian; Weigao Zhao (Science of The Total Environment, 2024)

Effect of sesbania gum on the rheological, textural, and microstructural characteristics of CaSO4-induced soy protein isolate gels - Ran Yang; Bin Yu; Laixue Ni; Yungang Cao; Qingqing Chai; Haiteng Tao; Zheng Zhang; Guimei Liu; Yunhui Cheng; Haibo Zhao; Bo Cui; Zhengzong Wu (Food Hydrocolloids, 2024)

Characteristics of conserved microRNAome and their evolutionary adaptation to regulation of immune defense functions in the spleen of silver carp and bighead carp - Yinli Zhao; Jinxing Gu; Ran Wu; Bianzhi Liu; Pengsheng Dong; Guangqing Yu; Daoquan Zhao; Guoxi Li; Zhenjiang Yang (Fish & Shellfish Immunology, 2024)

A review of carbon nanomaterials/bacterial cellulose composites for nanomedicine applications - Yingyu Liu; Haiyan Liu; Susu Guo; Yifan Zhao; Jin Qi; Ran Zhang; Jianing Ren; Huaiyi Cheng; Mingrui Zong; Xiuping Wu; Bing Li (Carbohydrate Polymers, 2024)

A Review on Dewatering of Dredged Sediment in Water Bodies by Flocculation Processes - Qi Chen; Fuyuan Ran; Qing Wei; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Water, Air, & Soil Pollution, 2024)

Tricotyledony in sand rice (Agriophyllum squarrosum) - Ruilan Ran; Xiaofeng Li; Hong Sun; Yujie Liu; Guoxiong Chen; Pengshan Zhao (Genetic Resources and Crop Evolution, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Nano-drug delivery system targeting FAP for the combined treatment of oral leukoplakia - Ran Li; Yingjiao Zhao; Tiantian Liu; Yanwei Li; Chaoqiong Wan; Ruifang Gao; Chen Liu; Xianqi Li; Bing Li (Drug Delivery and Translational Research, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Preliminary assessment of carbonic acid dissociation constants: Insights from observations in China's east coastal oceans - Ping Wang; Qicheng Meng; Liang Xue; Yuhang Zhao; Hao Qiao; He Hu; Qinsheng Wei; Ming Xin; Xiangbin Ran; Chenhua Han; Feng Zhou; Chunying Liu (Marine Environmental Research, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Multicopy expression of sigma factor RpoH reduces prodigiosin biosynthesis in Serratia marcescens FS14 - Xuezheng Zhao; Dongqing Xu; Wenxiao Xia; Menghua Hu; Xuede Peng; Xia Liu; Tingting Ran; Weiwu Wang (Antonie van Leeuwenhoek, 2023)

Simultaneous determination of twelve natural estrogens in dairy milk using liquid–liquid extraction and solid-phase extraction coupled with gas chromatography-mass spectrometry - De-ming Kong; Zhao Tang; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Yu Liu (Environmental Science and Pollution Research, 2023)

Core community drives phyllosphere bacterial diversity and function in multiple ecosystems - Ran Xue; Shan Liu; Erinne Stirling; Yiling Wang; Kankan Zhao; Haruna Matsumoto; Mengcen Wang; Jianming Xu; Bin Ma (Science of The Total Environment, 2023)

Characterization of a fermented dairy, sour cream: Lipolysis and the release profile of flavor compounds - Meng-Song Wang; Min Fan; An-Ran Zheng; Chao-Kun Wei; Dun-Hua Liu; Kiran Thaku; Zhao-Jun Wei (Food Chemistry, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

A mega study of antibiotics contamination in Eastern aquatic ecosystems of China: occurrence, interphase transfer processes, ecotoxicological risks, and source modeling - Abdul Qadeer; Guo Rui; Liu Yaqing; Dai Ran; Chengyou Liu; Dong Jing; Muhammad Anis; Mengyang Liu; Shuhang Wang; Xia Jiang; Xingru Zhao (Journal of Hazardous Materials, 2023)

A versatile organic silicate aluminum hybrid coagulant for broad-spectrum removal of heavy metal ions - Jin-Wei Liu; Tao Fu; Guang-Dong Sun; Xiao-Ran Shen; Sheng Liu; Yang He; Yi Xu; Hua-Zhang Zhao (Chemical Engineering Journal, 2023)

Depleted uranium induces thyroid damage through activation of ER stress via the thrombospondin 1-PERK pathway - Chang Shu; Jie Li; Suiyi Liu; Yong Li; Yonghong Ran; Yazhen Zhao; Juan Li; Yuhui Hao (Chemico-Biological Interactions, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Making waves: Opportunities and challenges of applying far-UVC radiation in controlling micropollutants in water - Jing Zhao; Emma M. Payne; Bryan Liu; Chii Shang; Ernest R. Blatchley; William A. Mitch; Ran Yin (Water Research, 2023)

Corrigendum to “Recent advances on bioactive compounds, biosynthesis mechanism, and physiological functions of Nelumbo nucifera” [Food Chem. 412 (2023) 135581] - Xu Zhao; Ran Zhao; Xiaojing Yang; Lihui Sun; Yongming Bao; Yuan Shuai Liu; Xingxun Liu (Food Chemistry, 2023)

Fluoride resistance capacity in mammalian cells involves global gene expression changes associate with ferroptosis - Yi Zhang; Yimin Fang; Shen Zhao; Jialong Wu; Chenkang Lu; Lai Jiang; Shujun Ran; Jia Wang; Fei Sun; Bin Liu (Chemico-Biological Interactions, 2023)

Soil aggregates, carbon and nitrogen distribution, and water infiltration as influenced by mulching practices in a laterite mango (Mangifera indica L.) orchard - Chengming Yan; Dongsheng An; Baoshan Zhao; Haiyang Ma; Yanan Liu; Ran Kong; Junbo Su (Journal of Soils and Sediments, 2023)

Healthy values and de novo domestication of sand rice ( Agriophyllum squarrosum ), a comparative view against Chenopodium quinoa - Pengshan Zhao; Xiaofeng Li; Hong Sun; Xin Zhao; Xiaohua Wang; Ruilan Ran; Jiecai Zhao; Yuming Wei; Xin Liu; Guoxiong Chen (Critical Reviews in Food Science and Nutrition, 2023)

Marine oil spill remediation by Candelilla wax modified coal fly ash cenospheres - Juan Sun; Ran Li; Xiaoyang Wang; Chaocheng Zhao; Quanwei Song; Fang Liu; Zihao Wang; Chunshuang Liu; Xiuxia Zhang (Chemosphere, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Observed Taylor cap around a seamount intensified by a surface mesoscale eddy in the Northwest Pacific - Yansong Liu; Qiang Ren; Fei Yu; Jianfeng Wang; Ran Wang; Feng Nan; Yanan Ding; Tongtong Zheng; Chuanzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Climate Dynamics, 2023)

Identification of key regulatory pathways and genes involved in the dynamic progression of pigmentation in Sinibrama taeniatus - Dengyue Yuan; Xiaoqin Liu; Siya Wang; Haoyu Wang; Junting Li; Zhe Zhao; Lan Wei; Linfeng Cheng; Ran Teng; Zhijian Wang (Frontiers in Marine Science, 2023)
Intorduction Coloration is a prominent trait in fish that is closely linked to their market value. Fish exhibit a diverse range of body colors, making them an excellent model for studying molecular mechanisms underlying pigmentation. Although regulatory pathways involved in pigmentation have been extensively studied in model fish such as zebrafish and medaka, the presence of varying chromatophore types across different fish species suggests that fish pigmentation mechanisms are not fixed. Therefore, more studies should be conducted on non-model fish. Sinibrama taeniatus is an endemic fish in the upper Yangtze River that is highly valued for its ornamental and edible properties. Methods In this study, we identified three chromatophore types in S. taeniatus and investigated changes in body color, chromatophores, and pigments at different developmental stages. Subsequently, RNA-seq analysis revealed that retinol metabolism, thyroid hormone synthesis, purine metabolism, and pyrimidine metabolism pathway are closely associated with pigmentation. Results Weighted gene co-expression network analysis (WGCNA) identified several hub genes, including mitf , wnt 9a , wnt10b , wnt11 , adcy5 , edn1 , adcy8 , and rdh8 , that may play an important role in pigmentation. Discussion Overall, our findings provide valuable insights into the role of genes and pathways in fish pigmentation and offer useful information for body color-based molecular breeding programs in aquaculture.

New insight into ZnO@ZIFs composite: an efficient photocatalyst with boosted light response ability and stability for CO2 reduction - Ran Zhao; Yahui Nie; Junyi Liu; Yuxi Wang; Ningbo Li; Qin Cheng; Ming Xia (Environmental Science and Pollution Research, 2023)

Research on quantitative method of fish feeding activity with semi-supervised based on appearance-motion representation - Yaqian Wang; Xiaoning Yu; Jincun Liu; Ran Zhao; Liu Zhang; Dong An; Yaoguang Wei (Biosystems Engineering, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Enhanced removal of organic matter from oxygen-pressure leaching solution by modified anode slime - Yuhu Li; Ran Liu; Yudong Yang; Sijie Yang; Yi Zhao (Journal of Cleaner Production, 2023)

Recent advances on bioactive compounds, biosynthesis mechanism, and physiological functions of Nelumbo nucifera - Xu Zhao; Ran Zhao; Xiaojing Yang; Lihui Sun; Yongming Bao; Yuan Shuai Liu; Andreas Blennow; Xingxun Liu (Food Chemistry, 2023)

Crystallographic oriented plating by using lithiophilic ionic additives in carbonate electrolyte for enabling high voltage lithium metal batteries - Qiwen Ran; Jintao Liu; Lei Li; Qiang Hu; Fuquan Nie; Hongyuan Zhao; Xingquan Liu (Chemical Engineering Journal, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

Nitrogen Alleviated the Deterioration of Rice Quality by Affecting the Accumulation of Grain Storage Protein Under Elevated Temperature - Yufei Zhao; Xuan Ran; Tongyang Yin; Hao Guo; Xiaoyang Zhang; Yingying Shen; Wenzhe Liu; Yanfeng Ding; She Tang (Journal of Plant Growth Regulation, 2023)

Effect of straw return with nitrogen fertilizer on photosynthetic characteristics and yield of rice in soda saline–alkali rice paddy fields - Xiangyu Meng; Cheng Ran; Baolong Liu; Zhexuan Zhao; Tianqi Bai; Mingming Zhao; Zhaowei Cheng; Guang Chen; Yanqiu Geng (Cereal Research Communications, 2023)

A data mining method to extract traffic network for maritime transport management - Zhao Liu; Hairuo Gao; Mingyang Zhang; Ran Yan; Jingxian Liu (Ocean & Coastal Management, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Multi-omics analysis revealed NMBA induced esophageal carcinoma tumorigenesis via regulating PPARα signaling pathway - Hu Zhang; Chao Zhao; Ying Zhang; Lu Lu; Wei Shi; Qian Zhou; Yuepu Pu; Shizhi Wang; Ran Liu; Lihong Yin (Environmental Pollution, 2023)

Efficient oxidation of ammonium to nitrogen gas via accelerated ClO• generation at TiO2/Ru-IrO2 bifacial electrode in a UV-driven photoelectrochemical system - Yi Liu; Ran Mao; Jingwei Hao; Kaifeng Wang; Ke Hu; Yuexin Cui; Xu Zhao (Chemical Engineering Journal, 2023)

Targeting autophagy receptors OPTN and SQSTM1 as a novel therapeutic strategy for osteoporosis complicated with Alzheimer's disease - Ran Duan; Chun-Gu Hong; Meng-Lu Chen; Xin Wang; Zhi-Lin Pang; Hui Xie; Zheng-Zhao Liu (Chemico-Biological Interactions, 2023)

p53 inhibits the Urea cycle and represses polyamine biosynthesis in glioma cell lines - Yuhong Zhao; Yingxi Chen; Ling Wei; Jianhua Ran; Kejian Wang; Shujuan Zhu; Qian Liu (Metabolic Brain Disease, 2023)

Cobalt chloride exposure disturbs spindle assembly and decreases mouse oocyte development potential - Si-Cheng Zhao; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhi-Ran Xu; Yu Liu (Toxicology, 2023)

Influence of habitats and physicochemical factors on trophic transfer processes of antibiotics in a freshwater ecosystem: Application of stable isotopes and human health risks - Abdul Qadeer; Zeeshan Ajmal; Liu Hanxia; Dai Ran; Tadiyose Girma Bekele; Kelly L. Kirsten; Sisi Liu; Mengyang Liu; Huang Zhifeng; Dong Jing; Shuhang Wang; Jiang Xia; et al. (Science of The Total Environment, 2023)

The study of Fengyun4A temperature profile data assimilation in a southwest vortex heavy rainfall case - Kuo Zhou; Lingkun Ran; Libo Zhou; Tianbao Zhao; Lei Chen; Haiwen Liu (Atmospheric Research, 2023)

QTL detection for internode diameter and its association with yield-related traits in wheat - Haitao Yu; Yanan Liu; Zongfeng Zou; Xusheng Sun; Jinshan Zhang; Shun Song; Lijie Wang; Ran Qin; Han Sun; Fa Cui; Chunhua Zhao; Shubing Shi (Cereal Research Communications, 2023)

Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Qiang Ren; Yansong Liu; Ran Wang; Feng Nan; Jianfeng Wang; Xinyuan Diao; Zifei Chen; Fei Yu; Chuangzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans; however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy–Kuroshio interactions based on large-scale in situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018–2019 (12 deployed east of Taiwan within a 3 × grid) were used to reveal the three-dimensional structure of mesoscale eddies and their interaction with Kuroshio. The results show a strengthening (weakening) of the tilt of the pycnocline, which has also caused a deeper (shallower) pycnocline in eastern Taiwan following an anticyclonic (cyclonic) interaction with Kuroshio, which resulted in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downward (upward) movement at the center of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for further research on energy exchange during eddy–Kuroshio interactions.

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Recent advancements in antibiotics containing wastewater treatment by integrated bio-electrochemical-constructed wetland systems (BES-CWs) - Shuang Luo; Zhi-Yuan Zhao; Ying Liu; Ran Liu; Wen-Zong Liu; Xiao-Chi Feng; Ai-Jie Wang; Hong-Cheng Wang (Chemical Engineering Journal, 2023)

Depleted uranium causes renal mitochondrial dysfunction through the ETHE1/Nrf2 pathway - Suiyi Liu; Shuang Wang; Yazhen Zhao; Juan Li; Chang Shu; Yong Li; Jie Li; Binghui Lu; Zeheng Xu; Yonghong Ran; Yuhui Hao (Chemico-Biological Interactions, 2023)

Can carbon emission trading pilot policy drive industrial structure low-carbon restructuring: new evidence from China - Bing Shen; Xiaodong Yang; Yang Xu; Wenfeng Ge; Guangliang Liu; Xufeng Su; Shikuan Zhao; Abd Alwahed Dagestani; Qiying Ran (Environmental Science and Pollution Research, 2023)

Innovative natural antimicrobial natamycin incorporated titanium dioxide (nano-TiO2)/ poly (butylene adipate-co-terephthalate) (PBAT) /poly (lactic acid) (PLA) biodegradable active film (NTP@PLA) and application in grape preservation - Yanli Zheng; Xiaoyu Jia; Zhiyong Zhao; Yalin Ran; Meijun Du; Haiyu Ji; Yanfang Pan; Ziqin Li; Xiaowei Ma; Yue Liu; Lihua Duan; Xihong Li (Food Chemistry, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Identification of mutational signature for lung adenocarcinoma prognosis and immunotherapy prediction - Sainan Zhang; Mengyue Li; Yilong Tan; Juxuan Zhang; Yixin Liu; Wenbin Jiang; Xin Li; Haitao Qi; Lefan Tang; Ran Ji; Wenyuan Zhao; Yunyan Gu; et al. (Journal of Molecular Medicine, 2022)

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

Sea ice recognition for CFOSAT SWIM at multiple small incidence angles in the Arctic - Meijie Liu; Ran Yan; Xi Zhang; Ying Xu; Ping Chen; Yongsen Zhao; Yuexiang Guo; Yangeng Chen; Xiaohan Zhang; Shengxu Li (Frontiers in Marine Science, 2022)
Sea ice recognition is one of the main tasks for sea ice monitoring in the Arctic and is also applied for the detection of other ocean phenomena. The Surface Wave Investigation and Monitoring (SWIM) instrument, as an innovative remote sensor that operates at multiple small incidence angles, is different from existing sensors with moderate and normal incidence modes for sea ice monitoring. Sea ice recognition at small incidence angles has rarely been studied. Moreover, SWIM uses a discrimination flag of sea ice and sea water to remove sea ice from sea wave products. Therefore, this research focuses on sea ice recognition in the Arctic based on SWIM data from October 2020 to April 2021. Eleven features are first extracted, and applied for the analysis of the waveform characteristics using the cumulative probability distribution (CPD) and mutual information measurement (MIM). Then, random forest (RF), k-nearest neighbor (KNN) and support vector machine (SVM) classifiers are built, and their abilities of sea ice recognition are assessed. The optimal classifier is the KNN method with Euclidean distance and k equal to 11. Feature combinations are also used to separate sea ice and sea water based on the KNN method to select the optimal combination. Thus, the optimal classifier-feature assembly at each small incidence angle is established, and the highest overall accuracy reaches 97.1%. Moreover, the application of the optimal classifier–feature assemblies is studied, and its performance is fairly good. These assemblies yield high accuracies in the short- and long-term periods of sea ice recognition, and the overall accuracies are greater than 93.1%. So, the proposed method satisfies the SWIM requirement of removing the sea ice effect. Moreover, sea ice extents and edges can be extracted from SWIM sea ice recognition results at a high level of precision greater than 94.8%. As a result, the optimal classifier–feature assemblies based on SWIM data express the effectiveness of the SWIM approach in sea ice recognition. Our work not only highlights the new sea ice monitoring technology of remote sensing at small incidence angles, but also studies the application of SWIM data in sea ice services.

Fine mapping of QFlw-5B, a major QTL for flag leaf width in common wheat (Triticum aestivum L.) - Chunhua Zhao; Xijian Liu; Hongwei Liu; Wenchao Kong; Zhuochao Zhao; Shengren Zhang; Saining Wang; Yingzi Chen; Yongzhen Wu; Han Sun; Ran Qin; Fa Cui (Theoretical and Applied Genetics, 2022)

Vegetation dynamics and its response to climate change during the past 2000 years in the Altai Mountains, northwestern China - Dongliang Zhang; Yunpeng Yang; Min Ran; Bo Lan; Hongyan Zhao; Qi Liu (Frontiers of Earth Science, 2022)

Design and synthesis of novel pyrazolopyrimidine-based derivatives as reversible BTK inhibitors with potent antiproliferative activity in mantle cell lymphoma - Fansheng Ran; Yang Liu; Guisen Zhao (Medicinal Chemistry Research, 2022)

The dysregulation of unsaturated fatty acid-based metabolomics in the MNNG-induced malignant transformation of Het-1A cells - Hu Zhang; Qiwei Liu; Chao Zhao; Ying Zhang; Shizhi Wang; Ran Liu; Yuepu Pu; Lihong Yin (Environmental Science and Pollution Research, 2022)

Categorizing objects from MEG signals using EEGNet - Ran Shi; Yanyu Zhao; Zhiyuan Cao; Chunyu Liu; Yi Kang; Jiacai Zhang (Cognitive Neurodynamics, 2022)

Numerical and Experimental Assessment of the Sandstone Fracture Mechanism by Non-uniform Bonded Particle Modeling - Kui Zhao; Wenkai Wu; Peng Zeng; Daoxue Yang; Yongguang Liu; Li Wang; Shanhu Ran (Rock Mechanics and Rock Engineering, 2021)

Neural responses to rapidly selecting color names with different novelty - Hanqing Ma; Yunyi Zhang; Jingyi Zhang; Yong Liu; Zhiliang Long; Huangyanqiu Ran; Jingwen Li; Yingmei Qin; Jia Zhao (Cognitive Neurodynamics, 2021)

Associations between essential microelements exposure and the aggressive clinicopathologic characteristics of papillary thyroid cancer - Ming-Jun Hu; Jia-Liu He; Xin-Ran Tong; Wan-Jun Yang; Huan-Huan Zhao; Guo-Ao Li; Fen Huang (BioMetals, 2021)

Effect of ambient air pollution on tuberculosis risks and mortality in Shandong, China: a multi-city modeling study of the short- and long-term effects of pollutants - Yao Liu; Shi Zhao; Yifan Li; Wanmei Song; Cuixiang Yu; Lei Gao; Jinjun Ran; Daihai He; Huaichen Li (Environmental Science and Pollution Research, 2021)

The evaluation of immobilization behavior and potential ecological risk of heavy metals in bio-char with different alkaline activation - Bing Zhao; Xinyang Xu; Wenbao Liu; Ran Zhang; Miao Cui; Jie Liu; Wenbo Zhang (Environmental Science and Pollution Research, 2021)

Interactions between invasive fungi and symbiotic bacteria - Fen Wang; Caiyan Xin; Jiexing Liu; Zhuonan Ran; Chunling Zhao; Zhangyong Song (World Journal of Microbiology and Biotechnology, 2020)

Annual 30-m land use/land cover maps of China for 1980–2015 from the integration of AVHRR, MODIS and Landsat data using the BFAST algorithm - Yidi Xu; Le Yu; Dailiang Peng; Jiyao Zhao; Yuqi Cheng; Xiaoxuan Liu; Wei Li; Ran Meng; Xinliang Xu; Peng Gong (Science China Earth Sciences, 2020)

Object-based change detection for VHR remote sensing images based on a Trisiamese-LSTM - Ran Jing; Shuang Liu; Zhaoning Gong; Zhiheng Wang; Hongliang Guan; Atul Gautam; Wenji Zhao (International Journal of Remote Sensing, 2020)

Doxorubicin sensitizes cancer cells to Smac mimetic via synergistic activation of the CYLD/RIPK1/FADD/caspase-8-dependent apoptosis - Chengkui Yang; Qiao Ran; Yifei Zhou; Shan Liu; Cong Zhao; Xiaoliang Yu; Fang Zhu; Yuting Ji; Qian Du; Tao Yang; Wei Zhang; Sudan He (Apoptosis, 2020)

Association of Corticotropin-Releasing Hormone Receptor-1 Gene Polymorphisms and Personality Traits with Violent Aggression in Male Adolescents - Li Liu; Yi Qiao; Yang Shao; Shun-ying Yu; Chen Zhang; Ran Zhang; Dong-xiang Wang; Min Zhao; Bin Xie (Journal of Molecular Neuroscience, 2020)

Identification of a candidate gene underlying qKRN5b for kernel row number in Zea mays L. - Xiaomeng Shen; Ran Zhao; Lei Liu; Can Zhu; Manfei Li; Hewei Du; Zuxin Zhang (Theoretical and Applied Genetics, 2019)

Automated Detection of Vulnerable Plaque for Intravascular Optical Coherence Tomography Images - Ran Liu; Yanzhen Zhang; Yangting Zheng; Yaqiong Liu; Yang Zhao; Lin Yi (Cardiovascular Engineering and Technology, 2019)

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

Analysis of status and countermeasures of cancer incidence and mortality in China - Chunchun Wu; Mengna Li; Hanbing Meng; Yukun Liu; Weihong Niu; Yao Zhou; Ran Zhao; Yumei Duan; Zhaoyang Zeng; Xiaoling Li; Guiyuan Li; Wei Xiong; et al. (Science China Life Sciences, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Formation and evolution of the tertiary carbonate reefs in the Madura Strait Basin of Indonesia - Weimin Ran; Xiwu Luan; Yintao Lu; Hong Liu; Jiajia Yang; Yang Zhao; Wenchang He; Zhonghui Yan (Journal of Oceanology and Limnology, 2019)

Using generalized additive models to investigate factors influencing cyanobacterial abundance through phycocyanin fluorescence in East Lake, China - Yi-Ming Kuo; Jun Yang; Wen-wen Liu; Enmin Zhao; Ran Li; Liquan Yao (Environmental Monitoring and Assessment, 2018)

Potential health risk assessment through ingestion and dermal contact arsenic-contaminated groundwater in Jianghan Plain, China - Ran Li; Yi-Ming Kuo; Wen-wen Liu; Cheng-Shin Jang; Enmin Zhao; Liquan Yao (Environmental Geochemistry and Health, 2018)

The biogenic silica composition, behavior and budget in the Changjiang Estuary - Xiangbin Ran; Jun Liu; Sen Liu; Jiaye Zang; Baodong Wang; Jun Zhao (Acta Oceanologica Sinica, 2018)

Seafood consumption among Chinese coastal residents and health risk assessment of heavy metals in seafood - Ran Zhao; Shuangshuang Yan; Min Liu; Bi Wang; Dong Hu; Dongbei Guo; Juan Wang; Wanting Xu; Chun Fan (Environmental Science and Pollution Research, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

MAPK cascade‐mediated regulation of pathogenicity, conidiation and tolerance to abiotic stresses in the entomopathogenic fungus M etarhizium robertsii - Xiaoxuan Chen; Chuan Xu; Ying Qian; Ran Liu; Qiangqiang Zhang; Guohong Zeng; Xin Zhang; Hong Zhao; Weiguo Fang (Environmental Microbiology, 2016)
Summary M etarhizium robertsii has been used as a model to study fungal pathogenesis in insects, and its pathogenicity has many parallels with plant and mammal pathogenic fungi. MAPK (Mitogen‐activated protein kinase) cascades play pivotal roles in cellular regulation in fungi, but their functions have not been characterized in M . robertsii . In this study, we identified the full complement of MAPK cascade components in M . robertsii and dissected their regulatory roles in pathogenesis, conidiation and stress tolerance. The nine components of the Fus3, Hog1 and Slt2‐ MAPK cascades are all involved in conidiation. The Fus3‐ and Hog1‐ MAPK cascades are necessary for tolerance to hyperosmotic stress, and the Slt2‐ and Fus3‐ MAPK cascades both mediate cell wall integrity. The Hog1 and Slt2‐ MAPK cascades contribute to pathogenicity; the Fus3‐ MAPK cascade is indispensable for fungal pathogenesis. During its life cycle, M . robertsii experiences multiple microenvironments as it transverses the cuticle into the haemocoel. RNA ‐seq analysis revealed that MAPK cascades collectively play a major role in regulating the adaptation of M . robertsii to the microenvironmental change from the cuticle to the haemolymph. The three MAPKs each regulate their own distinctive subset of genes during penetration of the cuticle and haemocoel colonization, but they function redundantly to regulate adaptation to microenvironmental change.

Paenibacillus chinensis sp. nov., isolated from maize (Zea mays L.) seeds - Yang Liu; Ran Zhao; Ronghuan Wang; Su Yao; Lei Zhai; Xin Zhang; Chuanyong Chen; Yanhua Cao; Tianjun Xu; Yuanyuan Ge; Jiuran Zhao; Chi Cheng (Antonie van Leeuwenhoek, 2016)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Isolation and characterization of 18 microsatellite loci in the Chinese Noctule bat, Nyctalus plancyi - Hao Liu; Yujie Ran; Hongyan Shi; Xiaodong Jia; Lin Zhao (Conservation Genetics Resources, 2015)

Chryseobacterium polytrichastri sp. nov., isolated from a moss (Polytrichastrum formosum), and emended description of the genus Chryseobacterium - Xin Yao Chen; Ran Zhao; Zhi Ling Chen; Lei Liu; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Knockdown of response gene to complement 32 (RGC32) induces apoptosis and inhibits cell growth, migration, and invasion in human lung cancer cells - Ran Xu; Chao Shang; Jungang Zhao; Yun Han; Jun Liu; Kuanbing Chen; Wenjun Shi (Molecular and Cellular Biochemistry, 2014)

Krüppel-like Factor 8 Ameliorates Alzheimer's Disease by Activating β-Catenin - Ran Yi; Benwei Chen; Jing Zhao; Xiaorong Zhan; Liming Zhang; Xiaomin Liu; Qi Dong (Journal of Molecular Neuroscience, 2014)

Atg5 regulates late endosome and lysosome biogenesis - JunYa Peng; Ran Zhang; YiTong Cui; HaoDong Liu; XiaoXin Zhao; Lei Huang; MingXu Hu; XiaoXi Yuan; BenYu Ma; XiaoWei Ma; Ueno Takashi; Komatsu Masaaki; et al. (Science China Life Sciences, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Endothelium-specific SIRT1 overexpression inhibits hyperglycemia-induced upregulation of vascular cell senescence - HouZao Chen; YanZhen Wan; Shuang Zhou; YunBiao Lu; ZhuQin Zhang; Ran Zhang; Feng Chen; DeLong Hao; Xiang Zhao; ZhiChen Guo; DePei Liu; ChihChuan Liang (Science China Life Sciences, 2012)

The cessation and detoxification effect of tea filters on cigarette smoke - JingQi Yan; XiaoJing Di; CaiYi Liu; HuiMin Zhang; XiouQin Huang; JunJing Zhang; Yan Zhao; LongZe Zhang; YanZhong Chang; YongLin Liang; Ran Tao; BaoLu Zhao (Science China Life Sciences, 2010)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Studies on the anti-psoriasis constituents of Oplopanax elatus Nakai - De-Qiang Dou; Xiao-Yan Hu; Yue-Ran Zhao; Ting-Guo Kang; Feng-Yun Liu; Hai-Xue Kuang; David C. Smith (Natural Product Research, 2009)

MicroRNA-128 inhibits glioma cells proliferation by targeting transcription factor E2F3a - Yu Zhang; Tengfei Chao; Ran Li; Wei Liu; Yang Chen; Xingqi Yan; Yanhua Gong; Bin Yin; Wei Liu; Boqing Qiang; Jizhong Zhao; Jiangang Yuan; et al. (Journal of Molecular Medicine, 2009)